2016
DOI: 10.1103/physreve.94.032601
|View full text |Cite
|
Sign up to set email alerts
|

Impact of volume transition on the net charge of poly-N-isopropyl acrylamide microgels

Abstract: We explore the electrostatic properties of poly-N-isopropyl acrylamide microgels in dilute, quasi-de-ionized dispersions and show that the apparent net charge of these thermosensitive microgels is an increasing function of their size, the size being conveniently varied by temperature. Our experimental results obtained in a combination of light scattering, conductivity, and mobility experiments are consistent with those obtained in Poisson-Boltzmann cell model calculations, effectively indicating that upon shri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 43 publications
5
36
1
1
Order By: Relevance
“…Such a sharp increase of σ ( T ) can be explained in terms of the simultaneous sharp decrease of the suspension viscosity due to the reduction of the microgel volume fraction, and/or attributed to an increase of the microgel charge density driven by the VPT, and the partial expulsion of condensed counterions from the inner part of the microgels, with a consequent increase of their effective charge above the VPT. However the latter hypothesis, conforming to reduced counterion condensation on the microgels, is in contrast with recently published results 54 suggesting that the effective charge of PNiPAM microgels is an increasing function of their size. Therefore, the increase in both mobility and conductivity seems rather the result of particle shrinkage, which causes a net increase of particle charge density, and a large concomitant increase of free space.…”
Section: Resultscontrasting
confidence: 98%
“…Such a sharp increase of σ ( T ) can be explained in terms of the simultaneous sharp decrease of the suspension viscosity due to the reduction of the microgel volume fraction, and/or attributed to an increase of the microgel charge density driven by the VPT, and the partial expulsion of condensed counterions from the inner part of the microgels, with a consequent increase of their effective charge above the VPT. However the latter hypothesis, conforming to reduced counterion condensation on the microgels, is in contrast with recently published results 54 suggesting that the effective charge of PNiPAM microgels is an increasing function of their size. Therefore, the increase in both mobility and conductivity seems rather the result of particle shrinkage, which causes a net increase of particle charge density, and a large concomitant increase of free space.…”
Section: Resultscontrasting
confidence: 98%
“…In contrast, a more mathematically rigorous approach showed that the net charge was decreased by the deswelling of the microgel because the short-ranged association between the charged microgel and the neighboring small ions became stronger, mainly because of the increasing bare charge density of the microgel [15]. The present study and other experiments of light scattering, phase behavior, and conductivity for microgel suspensions [16,17] support the latter theoretical prediction. For PNIPA microgel in the deswollen state, the environment inside the particle should be more hydrophobic because of the dehydration of the polymers, which may affect effective permittivity around the ionic groups in the microgel.…”
Section: Resultssupporting
confidence: 67%
“…The electrostatic and electrokinetic properties of the microgel are described by the net charge rather than by the bare charge. Recent theoretical and experimental studies have shown that the net charge of the microgel was affected by the swelling degree of the microgel [13,14,15,16,17]. Therefore, it is plausible to reconsider the assumption of the constant charge in the analysis of the electrophoretic data of the thermosensitive microgels as a function of temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Dispersions of PNIPAM colloids at different concentrations were prepared in deionized water starting from a low volume fraction solution, the particle number density of which was determined with confocal microscopy, as detailed in the next section. No salt was added to the samples and therefore the system carries a certain amount of charge [42]. In order to disperse the particles uniformly, the solution was mixed using a magnetic stirrer.…”
Section: A Samplesmentioning
confidence: 99%
“…The faster T-induced variation of the area fraction might lead to dynamical frustration that induces only a partial rearrangement of the structural organization of the fluid state. In addition it is possible that changes in the degree of charging of the system with temperature also affect the glass obtained via the temperature variation route [42], and that aspects of jamming physics start to affect solidification through temperature jumps [26,29]. The dynamics show even more pronounced displacements than in the melting process and are more pronounced for φ A = 0.69 compared to the particle number density route.…”
Section: Comparison Of the Particle Number Density And Radius Incrmentioning
confidence: 99%